Professional ethics and institutional governance: A critical review of their social impact - Octavio, Victor (2026)
This article proposes an alternative reading of professional ethics, understood as an institutional governance infrastructure, to explain why ethical principles do not always translate into practices with social impact. Drawing on a critical review of the academic literature, the study identifies three key contributions: (i) the decoupling between declared ethical commitments and organizational practices; (ii) the limits of formal ethics and compliance codes when they are not articulated with institutional coordination arrangements; and (iii) the role of ethics in the construction and evaluation of legitimacy within complex institutional environments. The discussion suggests that these limitations do not appear to be explained solely by normative deficits, but rather by governance failures that hinder the practical integration of ethics into professional action. Professional ethics is thus framed as a relational, contingent, and evaluative process shaped by institutional structures and agents. Finally, the article advances a research agenda oriented toward empirical studies of ethical governance mechanisms across different organizational contexts.